Improving Students’ Vocabulary Mastery: Strategy, Obstacles, and Problems - Urip Widodo; Sudarto Sudarto; Walyono Walyono; Tri Suyatno; Metta Puspita Dewi (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The objectives of this research are to: (1) elaborate the teacher strategy in improving students’ English vocabulary mastery; (2) analyze the obstacles faced by teacher in improving students’ English vocabulary mastery; (3) elaborate the difficulties faced by students in mastering English Vocabulary. This research is a qualitative research which is a kind of a case study. The subject of the research is the students at the primary level which is amount 13 students. In collecting the data is used observation, interview, and documentation. Validity test uses triangulation technique and resources. Data analysis technique uses 3 stages namely data reduction, data display, and conclusion. The results of this research are as follows: (1) teacher’s strategy in improving students’ English vocabulary mastery are by using games and audio-visual learning media; (2) the obstacles faced by teacher in improving students’ English vocabulary mastery are the diversity of the primary students in Pagentan the limitation of English text book in the Pagentan Buddhist Sunday school; (3) the difficulties faced by students in mastering English Vocabulary are lack ability in pronunciation, to write, and to spell.